An observational study to compare between conventional condom balloon catheter with CG balloon - Xess, Somila; Baghel, Preeti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Postpartum haemorrhage (PPH) is a life-threatening complication of delivery. The most common cause of PPH is uterine atony. Intrauterine balloon tamponade has been suggested as an effective, easily administered minimally invasive treatment option to control uterine bleeding while preserving the mother’s ability to bear additional children. Methods: Twenty women with normal vaginal delivery were studied over a period of six months, 10 were inserted conventional balloon tamponade and rest 10 were inserted CG balloon and outcome studied in terms of time to assemble, leakage, expulsion, lumen occlusion, volume of fluid used, time to arrest bleeding, cost, drainage port, inflation deflation interval. Results: Most of the women were para 4 or more, unbooked belonging to age group of 20-30. Mean time to assemble Condom balloon tamponade was 1.8min and that in CG balloon was 1.2 minute. There was leakage and expulsion in two and lumen occlusion in three in the conventional balloon catheter. In the second group there was no leakage ,lumen occlusion or expulsion . There is uterine drainage port present in CG balloon which is characteristic of it which helps in determining the actual blood loss in real time. The inflation deflation interval and mean volume of fluid are almost same in both the groups. Conclusions: Both conventional balloon and CG balloon are effective and lifesaving in low resource setting with few advantages of CG balloon over conventional balloon tamponade.